A framework for balancing MFI regulation - Fakir, Adnan M.S. (© 2015 International Journal of Business and Management Study, 2016)
This article was published in International Journal of Business and Management Study [©2015 International Journal of Business and Management Study] and the definite version is available at: https://goo.gl/ElpNts